Molecular recognition of N-acetyltryptophan enantiomers by β-cyclodextrin - Chatziefthimiou, Spyros D.; Inclán, Mario; Giastas, Petros; Papakyriakou, Athanasios; Yannakopoulou, Konstantina; Mavridis, Irene M. (Beilstein Journal of Organic Chemistry, 2017)
The enantioselectivity of β-cyclodextrin (β-CD) towards L- and D-N-acetyltryptophan (NAcTrp) has been studied in aqueous solution and the crystalline state. NMR studies in solution show that β-CD forms complexes of very similar but not identical geometry with both L- and D-NAcTrp and exhibits stronger binding with L-NAcTrp. In the crystalline state, only β-CD–L-NAcTrp crystallizes readily from aqueous solutions as a dimeric complex (two hosts enclosing two guest molecules). In contrast, crystals of the complex β-CD–D-NAcTrp were never obtained, although numerous conditions were tried. In aqueous solution, the orientation of the guest in both complexes is different than in the β-CD–L-NAcTrp complex in the crystal. Overall, the study shows that subtle differences observed between the β-CD–L,D-NAcTrp complexes in aqueous solution are magnified at the onset of crystallization, as a consequence of accumulation of many soft host–guest interactions and of the imposed crystallographic order, thus resulting in very dissimilar propensity of each enantiomer to produce crystals with β-CD.
Keywords: β-cyclodextrin; enantiomeric discrimination; N-acetyltryptophan; NMR; X-ray structure

Cyclodextrins and their complexes. Chemistry, analytical methods, applications - Dodziuk, H. (Wiley-VCH Verlag GmbH & Co. KGaA, 2006)

(untitled) - Davis, M. E.; Brewster, M. E. (Nat. Rev. Drug Discovery, 2004)

(untitled) - Kurkov, S. V.; Loftsson, T. (Int. J. Pharm., 2013)

(untitled) - Loftsson, T.; Duchêne, D. (Int. J. Pharm., 2007)

(untitled) - Stella, V. J.; He, Q. (Toxicol. Pathol., 2008)

(untitled) - Rubin, A.; Knadler, M. P.; Ho, P. P. K.; Bechtol, L. D.; Wolen, R. L. (J. Pharm. Sci., 1985)

(untitled) - Hamilton, J. A.; Chen, L. (J. Am. Chem. Soc., 1988)

(untitled) - Rekharsky, M.; Inoue, Y. (J. Am. Chem. Soc., 2000)

Current Challenges on Large Supramolecular Assemblies - Mavridis, I. M. (Influence of the Guest on the Packing of Dimeric ß-Cyclodextrin Complexes, 1999)

(untitled) - Giastas, P.; Yannakopoulou, K.; Mavridis, I. M. (Acta Crystallogr., Sect. B, 2003)

(untitled) - Harata, K. (Chem. Rev., 1998)

(untitled) - Harata, K.; Uekama, K.; Otagiri, M.; Hirayama, F. (Bull. Chem. Soc. Jpn., 1987)

(untitled) - Yannakopoulou, K.; Mentzafos, D.; Mavridis, I. M.; Dandika, K. (Angew. Chem., Int. Ed. Engl., 1996)

(untitled) - Makedonopoulou, S.; Yannakopoulou, K.; Mentzafos, D.; Lamzin, V.; Popov, A.; Mavridis, I. M. (Acta Crystallogr., Sect. B, 2001)

(untitled) - García Méndez, S.; Otero Espinar, F. J.; Luzardo Alvarez, A.; Longhi, M. R.; Quevedo, M. A.; Zoppi, A. (J. Inclusion Phenom. Macrocyclic Chem., 2016)

(untitled) - Aachmann, F. L.; Larsen, K. L.; Wimmer, R. (J. Inclusion Phenom. Macrocyclic Chem., 2012)

(untitled) - Tao, Y.; Dai, J.; Kong, Y.; Sha, Y. (Anal. Chem., 2014)

(untitled) - Alexander, J. M.; Clark, J. L.; Brett, T. J.; Stezowski, J. J. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Clark, J. L.; Stezowski, J. J. (J. Am. Chem. Soc., 2001)

(untitled) - Clark, J. L.; Booth, B. R.; Stezowski, J. J. (J. Am. Chem. Soc., 2001)

(untitled) - Lipkowitz, K. B.; Raghothama, S.; Yang, J. A. (J. Am. Chem. Soc., 1992)

(untitled) - Xiao, Q.; Lu, S.; Huang, C.; Su, W.; Huang, S. (Sensors, 2016)

(untitled) - Xu, J.; Wang, Q.; Xuan, C.; Xia, Q.; Lin, X.; Fu, Y. (Electroanalysis, 2016)

(untitled) - Qin, L.; He, X.-W.; Li, W.-Y.; Zhang, Y.-K. (J. Chromatogr. A, 2008)

(untitled) - Malta, L. F. B.; Cordeiro, Y.; Tinoco, L. W.; Campos, C. C.; Medeiros, M. E.; Antunes, O. A. C. (Tetrahedron: Asymmetry, 2008)

(untitled) - Job, P. (C. R. Hebd. Seances Acad. Sci., 1925)

(untitled) - Mentzafos, D.; Mavridis, I. M.; Le Bas, G.; Tsoucaris, G. (Acta Crystallogr., Sect. B, 1991)

(untitled) - Makedonopoulou, S.; Mavridis, I. M. (Acta Crystallogr., Sect. B, 2000)

(untitled) - Steiner, T.; Koellner, G. (J. Am. Chem. Soc., 1994)

(untitled) - Chatziefthimiou, S. D.; Yannakopoulou, K.; Mavridis, I. M. (CrystEngComm, 2007)

(untitled) - Hadjoudis, E.; Yannakopoulou, K.; Chatziefthimiou, S. D.; Paulidou, A.; Mavridis, I. M. (J. Photochem. Photobiol., A: Chem., 2011)

(untitled) - Paulidou, A.; Yannakopoulou, K.; Mavridis, I. M. (J. Inclusion Phenom. Macrocyclic Chem., 2010)

(untitled) - Zabel, V.; Saenger, W.; Mason, S. A. (J. Am. Chem. Soc., 1986)

(untitled) - Ivanova, B.; Spiteller, M. (Int. J. Biol. Macromol., 2014)

(untitled) - Steiner, T.; Koellner, G.; Gessler, K.; Wolfram, S. (J. Chem. Soc., Chem. Commun., 1995)

(untitled) - Gessler, K.; Steiner, T.; Koellner, G.; Saenger, W. (Carbohydr. Res., 1993)

(untitled) - Udachin, K. A.; Wilson, L. D.; Ripmeester, J. A. (J. Am. Chem. Soc., 2000)

(untitled) - Enright, G. D.; Udachin, K. A.; Ripmeester, J. A. (CrystEngComm, 2010)

(untitled) - Otwinowski, Z.; Minor, W. (Methods Enzymol., 1997)

(untitled) - Sheldrick, G. M.; Schneider, T. R. (Methods Enzymol., 1997)

The PyMOL Molecular Graphics System - DeLano, W. L. (DeLano Scientific LLC, 2002)

(untitled) - Kabsch, W. (Acta Crystallogr., Sect. D, 2010)

(untitled) - Navaza, J. (Acta Crystallogr., Sect. A, 1994)

(untitled) - Salomon-Ferrer, R.; Case, D. A.; Walker, R. C. (Wiley Interdiscip. Rev.: Comput. Mol. Sci., 2013)

(untitled) - Wang, J.; Wolf, R. M.; Caldwell, J. W.; Kollamn, P. A.; Case, D. A. (J. Comput. Chem., 2004)

(untitled) - Tsui, V.; Case, D. A. (Biopolymers, 2000)